Navy shipboard lasers the weapons of tomorrow - Griffith, Richard E.; Coughlin, Gillian L. (Nova Science Publisher's, 2011)
The Department of Defense's (DOD) development work on high-energy military lasers, has reached the point where lasers capable of countering certain surface and air targets at ranges of about a mile could be made ready for installation on Navy surface ships over the next few years. This book examines Navy shipboard laser technologies.